Balancing Convenience and Connection: Blending Law School Teaching and Learning During a Pandemic - Jill Howieson; Ben Di Sabato; Emmelie Sparkes; Vincent Mancini (Legal Education Review)
This article reports on the lived experiences of 30 students completing a two-week intensive course on Dispute Resolution (DR) at the University of Western Australia Law School in 2021. The course was delivered fully-online in the first week, and in a traditional face-to-face setting in the second week. The adoption of online learning was in response to a government-mandated lockdown to combat the ongoing COVID-19 pandemic. The pandemic created a new landscape for higher education providers, where teachers needed to implement rapid adjustments to the delivery of legal education. By providing students with activities designed to capture their experiences with face-to-face and online delivery modes in the context of DR, Law School staff were able to gain valuable insight into the life of a law student during this time. The qualitative and quantitative findings revealed that the transition to online delivery was in some ways paradoxical, as students reported both benefits and limitations. This article contributes to accumulating literature exploring the impact of online delivery of education within a law school context, highlighting the potential barriers and facilitators to effective implementation identified by students. Further inquiry remains imperative in a post COVID-19 landscape where online delivery is increasingly relevant.